Analisis Efektivitas Iklan Televisi dan Faktor yang Mempengaruhi Keputusan Pembelian Es Krim Wall’s Magnum Berdasarkan Karakteristik Gender (Studi Kasus Mahasiswa Program Strata-1 IPB) - Astriyani, Indri; Syamsun, Muhammad; Indrawan, R. Dikky (Jurnal Manajemen dan Organisasi, 2011)
Magnum Manufacturers need to consider the differences between women and men in decision-making purchase of Magnum ice cream. On this basis, the purpose of this study was to (1) Magnum television advertising effectiveness analysis in communicating the advertising message by gender in student-Tier 1, Bogor Agricultural University, (2) analyze the factors that influence the purchase of real students by gender in the purchase Wall's Magnum ice cream by student stratum-1 Institut Pertanian Bogor. Analysis of the data used are Consumer Decision Model (CDM) and Canonical Correlation Analysis with the help of MINITAB 14, SPSS for Windows version 16.0 , Ms Excel and STATISTICA 8.Results of canonical correlation analysis based on respondents generally produced three factors that most influence the purchase of real to buy Magnum ice cream, namely factors friend (0666), knowledge of attributes (0519), trust (0515), and advertising (0.56).The results of the analysis of students based on canonical correlation produced three factors that influence the purchase of real to buy cream of Magnum of ice, i.e., factor of student (0.816), confidence (0.736), and personality (0.725). In students, the most influential factor is the factor of sales people and advertisements.